(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
تـم تقييـم فاعلية 13 عزلة محلية من النيماتودا الممرضة للحشرات مخبرياً، 12 عزلة منها تتبع النوع Heterorhabditis bacteriophora (H.b)وواحدة تتبع النوع Steinernema cubanum (S.c)ضد يرقات حديثة الفقس لنوعي الكابنودس Capnodis carbonaria (C.c)وCapnodis tenebrionis (C.t). استخدم لذلك ثلاث نسب للطور المعدي (IJ) من النيماتودا 30 و 90 و 270 طور معدي/مل ماء لكل نوع من الكابنودس، وكرر كل منها 12 مرة حيث احتوى المكرر على 3 يرقات كابنودس. دلت النتائج على قدرة العزلات جميعها على قتل اليرقات بعد 2-3 أيام من العدوى. كما دلت على أن المقدرة الأعلى لقتل يرقات الكابنودس هي للعزلة 12 من (H.b) فبلغت نسبة قتلها ليرقة الكابنودس (C.c) 72% و86% و 94% عند النسب 30 و90 و270 طور معدي/مل على التوالي، وكانت العزلة 13 (S.c) هي الأقل قدرة أمراضية فبلغت نسبة قتل يرقات (C.c) 19% و50% و72% عند النسب ذاتها على التوالي. كما دلت النتائج على أن فاعلية العزلات ضد يرقات (C.t) متقاربة مع فاعليتها ضد يرقات (C.c). Efficacy of thirteen isolates of entomopathogenic nematodes (EPNs), 12 of them belongs to Heterorhabditis bacteriophora (H.b) and 1 to Steinernema cubanum (S.c) against neonate larvae of Capnodis carbonaria (C.c) and Capnodis tenebrionis (C.t) were evaluated in laboratory. Three application rates 30, 90 and 270 infective juveniles (IJ) of EPNs per 1ml distilled water for each species of Capnodis were used and replicated 12 times, each replicate contained 3 Capnodis larvae. Results showed that all EPNs isolates had a potential virulence to kill larvae of both species (C.c) and (C.t) 2-3 days after infection. Isolate 12 (H.b) was the most effective where 72%,86% and 94% of (C.c) larvae were killed at 30,90, and 270 IJ/1ml, respectively. Isolate 13 (S.c) was the lowest effective where 19%, 50% and 72% of larvae were killed, respectively. Killing percentage of both (C.c) and (C.t) were close.